The Contribution of Agility and Speed to the Playing Performance of Soccer Athletes in Bangkinang City - Rizky, Elfera; Ahmadi, Dedi; Abrasyi, Rendy (Universitas Muhammadiyah Enrekang, 2026)
This study aimed to determine the contribution of agility and speed to the soccer playing performance of Bangkinang City athletes. Soccer is a sport that emphasizes physical, technical, tactical, and mental abilities. These components are part of physical condition, which is very important. This study used a quantitative approach with a correlational method. The sample in this study consisted of 32 Bangkinang City soccer athletes selected using a total sampling technique. The instruments used were the Illinois Agility Test to measure agility, a 30 meter sprint test to measure speed, and a soccer performance assessment instrument consisting of a soccer skills test and observation using an assessment instrument covering passing, dribbling, ball control, shooting, and off-the-ball movement. Data analysis used correlation and multiple regression tests. The results showed that agility made a significant contribution to playing performance of 0.682, which is included in the strong category. Speed contributed to soccer playing performance by 0.641. Simultaneously, agility and speed contributed to soccer playing performance by 0.641. Thus, it can be concluded that agility and speed are important factors influencing the soccer playing performance of Bangkinang City athletes.